Right atrial remodelling and prognosis in patients with severe atrial functional tricuspid regurgitation - Soongu Kwak; Dong‐Jae Han; Seung‐Pyo Lee; Ho Young Hwang; Hyung‐Kwan Kim; Yong‐Jin Kim; Kyung Hwan Kim; Jae Woong Choi; Jun‐Bean Park (ESC Heart Failure)
Abstract Aims Atrial functional tricuspid regurgitation (AFTR) is increasingly recognized as a distinct cause of tricuspid regurgitation, yet data on outcomes and their determinants are limited. This study examines the prognostic role of right atrial (RA) remodelling in patients with severe AFTR. Methods and results This retrospective study included consecutive patients with severe AFTR. The primary outcome was all‐cause mortality. Cutoff values for RA and right ventricular (RV) sizes related to mortality were identified using receiver operating characteristic curves and maximally selected rank statistics. The cohort included 155 patients with severe AFTR, 96.1% of whom had atrial fibrillation. Of these, 121 received medical treatment, and 34 underwent surgery during follow‐up. In the medical management group, 42 deaths (34.7%) occurred over a median of 3.3 years. Patients with high RV end‐diastolic area and RA area indices (>14.5 cm2/m2 and >22 cm2/m2) had significantly lower survival compared to their counterparts (P = 0.012 and P = 0.001, respectively). Cox analyses demonstrated that increased RV end‐diastolic area and RA area indices were associated with higher mortality (RV end‐diastolic area index, per 1 cm2/m2 increase: adjusted hazard ratio 1.11, 95% confidence interval 1.02–1.22, P = 0.019; RA area index, per 1 cm2/m2 increase: adjusted hazard ratio 1.06, 95% confidence interval 1.02–1.10, P = 0.006). Mortality was highest in patients with both high RV end‐diastolic area index (>14.5 cm2/m2) and RA area index (>22 cm2/m2) and lowest in those with low values for both indices (P = 0.001). In the surgical intervention group, four post‐surgical deaths (11.8%) occurred exclusively in patients with both high RA area and RV end‐diastolic area indices. Conclusions RA and RV enlargement are poor prognostic factors in patients with severe AFTR. These findings underscore the importance of assessing RA and RV remodelling to optimize the timing of intervention in this population.